Scotland's pariah : the life and work of John Pinkerton, 1758-1826 - O'Flaherty, Patrick, 1939-2017 (University of Toronto Press, 2015)
Scotland's Pariah is the first book to examine the remarkable life of John Pinkerton: antiquarian, poet, forger, cartographer, historian, serial adulterer, bigamist, and religious skeptic.